Public Health Interventions Delivered by Pharmacy Professionals in Low- and Middle-Income Countries in Africa: A Systematic Scoping Review - Begashaw Melaku Gebresillassie; Kelly Howells; Diane Ashiru-Oredope (MDPI AG, 2023)
Pharmacists and their teams play an important role in providing public health services, however little is known about their level of contribution and the strength of evidence in Africa's Low- and Middle-Income Countries (LMICs). The purpose of this scoping review was to explore and map the available evidence on pharmacy professional-delivered public health interventions in Africa's LMICs. Six electronic databases (Medline, Embase, International Pharmaceutical Abstract, PsycInfo, Maternity and Infant Care, and Cochrane database), relevant grey literature sources, key journals focused on African health issues, and libraries of relevant organizations were searched between January 2010 and December 2020. Studies were included if they reported public health interventions delivered by pharmacy professionals (pharmacists or pharmacy technicians) or their teams. The quality of the individual studies was assessed using an adapted grading system. Thirty-nine studies were included in this review. Pharmacy professionals delivered a wide range of public health interventions, with the most common themes being noncommunicable diseases, infectious diseases, sexual and reproductive health, antimicrobial resistance, and other health conditions, e.g., dental health, unused drugs or waste, minor ailments. The majority of the studies were classified as low-quality evidence. They were predominantly feasibility and acceptability studies conducted in a narrow study area, in a small number of LMICs in Africa, resulting in little evidence of service effectiveness, issues of broad generalizability of the findings, and sustainability. The major constraints to service provision were identified as a lack of training, public recognition, and supporting policies. Pharmacy professionals and their teams across LMICs in Africa have attempted to expand their practice in public health. However, the pace of the expansion has been slow and lacks strong evidence for its generalizability and sustainability. Future research is needed to improve the quality of evidence, which will subsequently serve as a foundation for policy reform, allowing pharmacy professionals to make significant contributions to the public health initiatives in the region.